Development of New Technologies for Integrated Transport Chains in Europe - Woxenius, Johan (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
Transport systems are designed according to geographical and infrastructural conditions as well as the demand for transport services in terms of goods flow and desired transport quality. Thorough knowledge about these factors is especially important for developers of integrated transport chains that must consider the preconditions for all links and nodes in the transport chain. Due to the additional costs of terminal handling and local road haulage, transport relations must exceed a certain minimum distance to allow CT to compete with pure road transport. This implies that international CT is of greater importance than domestic CT for most European countries and compatibility between national networks is of utmost importance. Contrary to this fact, transfer technology development is by many still considered to be governed by national policies and preconditions. This paper aims at describing the national features that logically should guide the development of combined transport transshipment technology, national and EU research and development support measures and, finally, to analyse whether national or international conditions are prevailing for a number of current development projects. The presentation is focused on the transshipment function, as shown in the simple system model presented in figure 1, regardless of whether it is terminal-based or integrated with a vehicle or a load carrier.